X+6=4x+11

Simple and best practice solution for X+6=4x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+6=4x+11 equation:



X+6=4X+11
We move all terms to the left:
X+6-(4X+11)=0
We get rid of parentheses
X-4X-11+6=0
We add all the numbers together, and all the variables
-3X-5=0
We move all terms containing X to the left, all other terms to the right
-3X=5
X=5/-3
X=-1+2/3

See similar equations:

| 3m+100=450 | | 4j-4j=9 | | 5(m-91)-52=87 | | -6(6x+2)=2x+26 | | 3m+500=438 | | P+52=3p | | 21=−3(x−1) | | 2/3y+5=2/3(y+9) | | 7x-4=-34 | | 12+4d=16d-12 | | -40=4(x-100) | | 8=g-7 | | F(-2x)=15x-8 | | -7+6j=7j | | 4g-17=27 | | -8w+10=-6(w-3) | | 3m+100=438 | | 1/2x-5=-8 | | b÷4=32 | | -35+3x=45+5x | | 12/72=x/12 | | -4/3w+17=11 | | 1/5(20-5y)=6 | | 10y+25=45 | | 3+3(3x-6)=5-4(2x+1) | | 3v=4v−10 | | 3x62/5=13 | | 6=8-c | | 4(3x-)=16 | | -8u+6(u-2)=-14 | | 8d-4d+5=-3 | | 3=3u−6 |

Equations solver categories